NILAI-NILAI FUNGSIONAL PERPUSTAKAAN DESA DALAM PEWARISAN HASIL KARYA BUDAYA LOKAL - Yusup, Pawit M; Winoto, Yunus; Komariah, Neneng (Edulib, 2017)
Abstract. Records the history and culture of a region in the past stored in various forms of printed and recorded, partly managed by the library; some are still stored in various places, including West Java in the form of historical sites and culture. Form of work in question can bebooks, magazines, newspapers, maps, brochures, and the like, both in print and digital format. These works contain a benefit for knowledge and education. Meanwhile, the library as an institution in charge of managing printed and recorded works, including ancient works, continues to contribute in this work with storage for wider dissemination. This study examines the existence of public libraries and village libraries in West Java related to its role as referred to above. The method used is direct observation to the field. The result illustrates that public libraries and village libraries already participate to provide this type of collection for the benefit of the public on the current generation and the future.Keywords: Printed Materials, Paper records, Ancient manuscripts,Cultural Values, Public Library.